(untitled) (Journal of Asian Development Studies, 2024)
The present study examines differences in psychological distress and marital adjustment between spouses of Hepatitis C patients based on socioeconomic and gender status, specifically addressing dissimilarities in emotional and couple functioning due to economic and gender disparities. Hepatitis C is a chronic and progressive disease, and there is a substantial caregiver burden required, which should increase stress and negatively impact marital quality. With the data collected from 200 spouses of Ayub Medical Complex and Combined Military Hospital Abbottabad Pakistan, this research investigates the moderating effects of economic resources and gender roles on psychological distress and other factors pertinent to marital satisfaction, such as affection expressing marital adjustment and dyadic cohesion. Results identified by the study show that compared to spouses with higher SES, participants with lower SES have significantly elevated levels of psychological distress and reduced marital adjustment, indicating the role of economic stress in caregiver stress. The female spouses continue to display higher levels of distress and lower marital satisfaction and cohesiveness than male spouses, replicating the usual female gender role expectations of the traditional caregiver. Also, gender and economic level crosstabulations show differences in coping and support seeking and, hence, mental health and relationship quality. These results indicate the further imperative of targeting specific psychological and social support for economically disadvantaged and female carers to alleviate their specific known burdens, providing a foundation for developing policies dealing with marital stress in chronic illness situations, among other proposals